Pure Trans-Resveratrol Nanoparticles Prepared by a Supercritical Antisolvent Process Using Alcohol and Dichloromethane Mixtures: Effect of Particle Size on Dissolution and Bioavailability in Rats - Eun-Sol Ha; Heejun Park; Seon-Kwang Lee; Woo-Yong Sim; Ji-Su Jeong; In-hwan Baek; Min-Soo Kim (MDPI AG, 2020)
The aim of this study was to prepare pure trans-resveratrol nanoparticles without additives (surfactants, polymers, and sugars) using a supercritical antisolvent (SAS) process with alcohol (methanol or ethanol) and dichloromethane mixtures. In addition, in order to investigate the effect of particle size on the dissolution and oral bioavailability of the trans-resveratrol, two microparticles with different sizes (1.94 μm and 18.75 μm) were prepared using two different milling processes, and compared to trans-resveratrol nanoparticles prepared by the SAS process. The solid-state properties of pure trans-resveratrol particles were characterized. By increasing the percentage of dichloromethane in the solvent mixtures, the mean particle size of trans-resveratrol was decreased, whereas its specific surface area was increased. The particle size could thus be controlled by solvent composition. Trans-resveratrol nanoparticle with a mean particle size of 0.17 μm was prepared by the SAS process using the ethanol/dichloromethane mixture at a ratio of 25/75 (w/w). The in vitro dissolution rate of trans-resveratrol in fasted state-simulated gastric fluid was significantly improved by the reduction of particle size, resulting in enhanced oral bioavailability in rats. The absolute bioavailability of trans-resveratrol nanoparticles was 25.2%. The maximum plasma concentration values were well correlated with the in vitro dissolution rate. These findings clearly indicate that the oral bioavailability of trans-resveratrol can be enhanced by preparing pure trans-resveratrol nanoparticles without additives (surfactants, polymers, and sugars) by the SAS process. These pure trans-resveratrol nanoparticles can be applied as an active ingredient for the development of health supplements, pharmaceutical products, and cosmetic products.